Endocrinological characterization of an ovarian sex cord–stromal tumor with a Sertoli cell pattern in a Japanese Black cow. Issue 11 (17th September 2019) - El‐Sheikh Ali, Hossam; Kitahara, Go; Nibe, Kazumi; Osawa, Takeshi
Abstract: A Japanese Black cow was evaluated for prolonged post‐partum anestrus and enlargement of the right ovary. Transrectal ultrasonography revealed that the right ovary was markedly enlarged and had a solid appearance, while the left ovary was small and inactive. The presumptive diagnosis was directed towards granulosa‐theca cell tumour (GTCT) which was supported by markedly elevated plasma anti‐Müllerian hormone (AMH; 332.0 ng/ml), oestradiol (E2 ; 103.3 pg/ml) and immunoreactive inhibin (ir‐INH; 2.1 ng/ml) in comparison with the diagnostic cut‐off points for bovine GTCTs. Since the cow had been infertile and had swelling of the udder, slaughter was chosen. Histopathological examination revealed that the tumour was an ovarian sex cord–stromal tumour (SCST) with a Sertoli cell pattern. These findings suggest that plasma AMH, ir‐INH and E2 could be possible biomarkers for bovine ovarian SCST with a Sertoli cell pattern, whereas this case could not be distinguished from GTCTs based on endocrinological profile.